Minimalist Approach to Perceptual Interactions - Lenay, Charles (Frontiers in Human Neuroscience, 2012)
Work aimed at studying social cognition in an interactionist perspective often encounters substantial theoretical and methodological difficulties: identifying the significant behavioural variables; recording them without disturbing the interaction; and distinguishing between: (a) the necessary and sufficient contributions of each individual partner for a collective dynamics to emerge ; (b) features which derive from this collective dynamics and escape from the control of the individual partners ; (c) the phenomena arising from this collective dynamics which are subsequently appropriated and used by the partners. We propose a minimalist experimental paradigm as a basis for this conceptual discussion: by reducing the sensory inputs to a strict minimum, we force a spatial and temporal deployment of the perceptual activities, which makes it possible to obtain a complete recording and control of the dynamics of interaction. After presenting the principles of this minimalist approach to perception, we describe a series of experiments on two major questions in social cognition: recognizing the presence of another intentional subject; and phenomena of imitation. In both cases, we propose explanatory schema which render an interactionist approach to social cognition clear and explicit. Starting from our earlier work on perceptual crossing we present a new experiment on the mechanisms of reciprocal recognition of the perceptual intentionality of the other subject: the emergent collective dynamics of the perceptual crossing can be appropriated by each subject. We then present an experimental study of opaque imitation (when the subjects cannot see what they themselves are doing). This study makes it possible to characterize what a properly interactionist approach to imitation might be. In conclusion, we draw on these results, to show how an interactionist approach can contribute to a fully social approach to social cognition.